a)43 + 25 + (−43) + (−26)
b)(−20). 9. (−50). 7
c)85.39 + 85.61 − 300
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(b,\left(-34\right)-9-26\\ =\left(-34-26\right)-9\\ =-60-9\\ =-69\\ c,57-\left(-43\right)\\ =57+43\\ =100\\ d,\left(-25\right).42+\left(-25\right).58\\ =\left(-25\right).\left(42+58\right)\\ =-25.100\\ =-2500\\ g,48+79-48-\left(-21\right)\\ =\left(48-48\right)+\left(79+21\right)\\ =0+100\\ =100\\ h,7+30-\left(-15\right)-7\\ =\left(7-7\right)+\left(30+15\right)\\ =0+45=45\)
a . 25 − 58 − 9 = - 31 b . 1 − ( 26 + 3 ) = - 28 c . 12.15 − 12.5 = 120 d . 10 − [ 12 − ( − 9 − 1 ) ] = -12 e . ( 38 − 29 + 43 ) − ( 43 + 38 ) = - 29 f . 2575 + 37 − 2576 − 29 = 7
1+2+3+4+5+6+7+8+9+10+11+12+13+14+15+16+17+18+19+20+21+22+23+24+25+26+27+28+29+30+31+32+33+34+35+36+37+38+39+40+41+42+43+44+45+46+47+48+49+50=1275
a, \(\left(-23\right).43+\left(-23\right).65-\left(-23\right).8\\ =\left(-23\right).\left(43+65-8\right)\\ =\left(-23\right).100=-2300\)
b,\(\left(-43\right).25+25.\left(-19\right)+25.\left(-38\right)\\ =25.\left[\left(-43\right)+\left(-19\right)+\left(-38\right)\right]\\ =25.\left(-100\right)=-2500\)
c,\(\left(-26\right).13+86.\left(-26\right)+\left(-26\right)\\ =\left(-26\right).\left(13+86+1\right)\\ =\left(-26\right).100=-2600\)
d,\(\left(-17\right).39+\left(-17\right)+\left(-17\right).60\\ =\left(-17\right).\left(39+1+60\right)\\ =\left(-17\right).100=-1700\)
a) (-32) . 43 + (-32) . 65 - (-32) . 8
= (-32) . (43 + 65 - 8)
= (-32) . 100
= -3200
b) (-43) . 25 + 25 . (-19) + 25 . (-38)
= 25 . [(-43) + (-19) + (-38)]
= 25 . (-100)
= -2500
c) (-26) . 13 + 86 . (-26) + (-26)
= (-26) . (13 + 86 + 1)
= (-26) . 100
= -2600
d) (-17) . 39 + (-17) + (-17) . 60
= (-17) . (1 + 39 + 60)
= (-17) . 100
= -1700
a) \(x+5=20-\left(12-7\right)\)
\(\Rightarrow x+5=20-5\)
\(\Rightarrow x+5=15\)
\(\Rightarrow x=15-5\)
\(\Rightarrow x=10\)
b) \(15-\left(3+2x\right)=2^2\)
\(\Rightarrow3+2x=15-4\)
\(\Rightarrow3+2x=11\)
\(\Rightarrow2x=11-3\)
\(\Rightarrow2x=8\)
\(\Rightarrow x=\dfrac{8}{2}\)
\(\Rightarrow x=4\)
c) \(-11-\left(19-x\right)=50\)
\(\Rightarrow19-x=-11-50\)
\(\Rightarrow19-x=-61\)
\(\Rightarrow x=61+19\)
\(\Rightarrow x=80\)
d) \(159-\left(25-x\right)=43\)
\(\Rightarrow25-x=159-43\)
\(\Rightarrow25-x=116\)
\(\Rightarrow x=25-116\)
\(\Rightarrow x=-91\)
e) \(\left(79-x\right)-43=-\left(17-52\right)\)
\(\Rightarrow\left(79-x\right)-43=52-17\)
\(\Rightarrow79-x-43=35\)
\(\Rightarrow36-x=35\)
\(\Rightarrow x=1\)
f) \(\left(7+x\right)-\left(21-13\right)=32\)
\(\Rightarrow7+x-8=32\)
\(\Rightarrow x-1=32\)
\(\Rightarrow x=32+1\)
\(\Rightarrow x=33\)
g) \(-x+20=-15+8+13\)
\(\Rightarrow-x+20=6\)
\(\Rightarrow x=20-6\)
\(\Rightarrow x=14\)
h) \(-\left(-x+13-142\right)+18=55\)
\(\Rightarrow x-13+142+18=55\)
\(\Rightarrow x+147=55\)
\(\Rightarrow x=55-147\)
\(\Rightarrow x=-92\)
a) (-37)+14+26+37 = ( -37 + 37) + ( 14 + 26) = 40
b) (-24)+6+10+24 = ( - 24 + 24) + ( 6 + 10) = 16
c) 15+23+9-25)+(-33) = (15 - 25) + ( 23 - 33) + 9
= - 10 - 10 + 9
= - 11
d) 60+33+(-50)+(-33) = ( 60 -50) + ( 33 - 33)
= 10
e) (-16)+(-209)+(-14)+209 = ( - 16 - 14) + ( - 209 + 209)
= - 30
g) (-12)+(-13)+36+(-11)= ( - 11 -12 - 13 ) + 36
= - 36 + 36 = 0
h) -16+24+16-34 = ( - 16 + 16)+(24 - 34) = - 10
r) 25+37-48-25-37 = (25 - 25)+(37 - 37) - 48 = - 48
u) 2575+37-2576-29 = ( 2575 - 2576) + ( 37 - 29)
= - 1 + 8 = 7
i) 34+35+36+37-14-15-16-17 = ( 34 - 14 )+(35 - 15)+(36-16)+ (37 - 17)
= 80
2 . Bỏ ngoặc rồi tính
a)-7264+(1543+7264) = - 7264 + 1543 + 7264
= 1543
b) (144-97)-144 = 144 - 97 - 144 = - 97
c) (-145)-(18-145) = - 145 - 18 + 145 = - 18
d) 11+(-11+27) = 11 - 11 + 27 = 27
e) (27+514)-(486-73) = 27 + 514 - 486 + 73
= 128
g) (36+79)+(145-79-66) = 36 + 79 + 145 - 79 - 66
= 115
h) 10-[12-(-9-1) = 10 - ( 12 + 9 + 1)
= 10 - 22
= - 12
r) (-28-29+43)-(43+38) = - 28 - 29 + 43 - 43 - 38
= - 95
u ) 271 - [(-43)+271-(-17)] = 271 + 43 - 271 - 17 = 26
i ) -144-[29-(+144)-(+144) = - 144 - 29 - 144 + 144 = -173
x - {34 - [26 + ( -66 - x)]} = 27 - { 43 + [ 25 - (20 - x )]}
⇔x - {34 - [26 - 66 -x ]} = 27 - { 43 + [25 - 20 - x]}
⇔x - {34 - 26 + 66 + x} = 27 - {43 + 25 - 20 - x}
⇔x - {74 + x} = 27 - {47 - x}
⇔x - 74 + x = 27 - 47 + x
⇔(x-x) -74 = x -20
⇔-74 =x -20
⇒ x = -74 +20 =-54
\(x-\left\{34-\left[-40-x\right]\right\}=27-\left\{43+5+x\right\}\\ \Leftrightarrow x-\left\{74+x\right\}=-21-x\\ \Leftrightarrow-21-x=-74\\ \Leftrightarrow-x=-53\\ \Leftrightarrow x=53\)
a)43 + 25 + (−43) + (−26)
=(43-43)+(25-26)
=-1
b)(−20). 9. (−50). 7
=[(-20).(-50)].9.7
=100.63
=6300
c)85.39 + 85.61 − 300
=85.(39+61)-300
=85.100-300
=8500-300
=8200